Profesionalitas Aparatur Sekretariat Daerah di Kabupaten Sumbawa Besar - JUANDA, KHAIRY (Jurnal Studi Pemerintahan, 2010)
The aim of this research is knowing the profesionality of aparature at local secretary ofSumbawa region in doing their work depend on function and job description. Beside that,this research try to know some obstacles and find the solution to increase aparatureprofesionality at Sekretariat Daerah Kabupaten Sumbawa. This reseach’s title is aProfesionality of aparature at local secretary of Sumbawa region. Research methods isused descriptive survey, documentation, Questioner, interview. The respondents of thisresearch are civil servant at Sekretariat Daerah Kabupaten Sumbawa. From this researchknew that civil servant competency is good, Acuntability is good, Recruitment is fair,Education level is poor. The conclution is aparature’s profesionality at local secretary of Sumbawa region in fair level.K